Anxiety in hospitalised families: lessons from the early phase of the COVID-19 pandemic - Annushkha Sinnathamby; Siau Hwei Ng; Amanda Zain; Liangjian Lu; Celeste Yong; Xinyi Thong; Si Min Chan (Singapore Medical Journal, 2025)
Introduction: In the early phase of the coronavirus disease 2019 (COVID-19) pandemic, children with COVID-19 in Singapore required hospital isolation. We aimed to explore the psychological experiences of children and their caregivers isolated in a tertiary university hospital due to COVID-19. Methods: A prospective mixed-methods design was used to evaluate the psychological status of hospitalised family units with one or more children aged <18 years who had severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Patient medical records were reviewed for demographic and clinical information. Parents and children ≥7 years of age underwent a psychologist-administered telephone-based interview. Self-reported, age-appropriate instruments, Short Mood and Feelings Questionnaire, and Screen for Adult/Child Anxiety-Related Disorders, were used to assess anxiety and depression, respectively. Participants were also interviewed qualitatively. Results: Fifteen family units were hospitalised between March 2020 and May 2020. Of these, 13 (73%) family units were recruited. The median age of the children and median hospitalisation duration were 57 months and 21 days, respectively. Median number of COVID-19 polymerase chain reaction swabs performed for each child was eight. All children had asymptomatic to mild SARS-CoV-2 disease. The criteria indicative of anxiety disorder were met by 40% of adults and 80% of children, while the criteria indicative of separation anxiety were met by 60% of parents and 100% of children. One child met the criteria indicative of depression. Uncertainty, separation, prolonged hospitalisation and frequent swabs caused significant reported anxiety. Conclusions: Families, especially children, had heightened anxiety while in hospital isolation. Therefore, home-based recovery from COVID-19 and psychological support for children and their families, with focus on early recognition of anxiety disorders, are recommended. We support review of paediatric isolation policy as the pandemic evolves.